Patient-reported outcomes - Johnston, Bradley C. (2019)
Authors of systematic reviews that include patient-reported outcomes (PROs) should have a good understanding of how patient-reported outcome measures (PROMs) are developed, including the constructs they are intended to measure, their reliability, validity and responsiveness. This chapter describes the category of outcomes known as PROs and their importance for healthcare decision making, and illustrates the key issues related to reliability, validity and responsiveness that systematic review authors should consider when including PROs. It also addresses the structure and content of PROs and provides guidance for combining information from different PROs. The chapter outlines a step-by-step approach to addressing each of these elements in the systematic review process. The focus is on the use of PROs in randomized trials, and what is crucial in this context when selecting PROs to include in a meta-analysis. The chapter describes PROMs in more detail and discusses some issues to consider when deciding which PROMs to address in a review.